Paradise of the Blind - Duong Thu Huong (New York, NYUnited States HarperCollins Publishers Inc, 2003)
Paradise of the Blind is an exquisite portrait of three Vietnamese women struggling to survive in a society where subservience to men is expected and Communist corruption crushes every dream. Through the eyes of Hang, a young woman in her twenties who has grown up amidst the slums and intermittent beauty of Hanoi, we come to know the tragedy of her family as land reform rips apart their village. When her uncle Chinh's political loyalties replace family devotion, Hang is torn between her mother's appalling self-sacrifice and the bitterness of her aunt who can avenge but not forgive. Only by freeing herself from the past will Hang be able to find dignity -- and a future.
Keywords: War -- War